The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/ac0401422
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Enantioseparation and Tandem UV−MS Detection of Eight β-Blockers in Micellar Electrokinetic Chromatography Using a Chiral Molecular Micelle

Abstract: The feasibility of using a new and more versatile polymeric chiral surfactant, i.e., poly(sodium N-undecenoxy carbonyl-L-leucinate (poly-L-SUCL) is investigated for simultaneous enantioseparation and detection of eight structurally similar beta-blockers with tandem UV and MS detection. Three optimization approaches, i.e., direct infusion-MS, capillary zone electrophoresis-MS, and chiral micellar electrokinetic chromatography-mass spectrometry (CMEKC-MS), were investigated to optimize sheath liquid parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 32 publications
4
83
0
Order By: Relevance
“…On the other hand, polymeric surfactants (also called molecular micelles or micelle polymers) are very attractive as alternative pseudostationary phases to conventional micelles for the coupling of the MEKC separation mode with ESI-MS [44][45][46]. They provide several advantages over conventional micelles for this hyphenation [44,45]: (i) the covalent bonds between surfactant monomers are difficult to ionize in the electrospray resulting in less-background noise from surfactant monomers of low molecular weights in MEKC-MS applications, (ii) micellar solutions can be used at any polymer concentration due to zero CMC, consequently higher S/N are observed in MEKC-ESI-MS, and (iii) polymeric surfactants have lower surface activity and lower volatility, and are stable in the presence of a high content of organic modifier in the BGE, which also tends to enhance the ESI-MS intensity.…”
Section: End-column Detection In Chiral Analysis By Cementioning
confidence: 99%
“…On the other hand, polymeric surfactants (also called molecular micelles or micelle polymers) are very attractive as alternative pseudostationary phases to conventional micelles for the coupling of the MEKC separation mode with ESI-MS [44][45][46]. They provide several advantages over conventional micelles for this hyphenation [44,45]: (i) the covalent bonds between surfactant monomers are difficult to ionize in the electrospray resulting in less-background noise from surfactant monomers of low molecular weights in MEKC-MS applications, (ii) micellar solutions can be used at any polymer concentration due to zero CMC, consequently higher S/N are observed in MEKC-ESI-MS, and (iii) polymeric surfactants have lower surface activity and lower volatility, and are stable in the presence of a high content of organic modifier in the BGE, which also tends to enhance the ESI-MS intensity.…”
Section: End-column Detection In Chiral Analysis By Cementioning
confidence: 99%
“…The difference between conventional micelles and micelle polymers can be seen in Fig. 1 where the resulting PSPs were used for MEKC-ESI-MS analyses [43].…”
Section: Micellesmentioning
confidence: 99%
“…The use of chiral polymeric micelles as chiral selectors in MEKC-ESI-MS, the second such study, was published in 2005 by Akbay et al [43]. Poly(sodium N-undecenoxycarbonyl-L-leucinate (poly-L-SUCL) was synthesized and employed for the concurrent testing of eight b-blockers.…”
Section: Micellesmentioning
confidence: 99%
“…39-41 Recently, our group conducted several studies with the chiral amino acid based polymeric surfactant which actually showed at least 5-14 fold better sensitivity in MEKC-MS compared to MEKC-UV method for chiral analysis. 31,[40][41] The pH is considered one of the most important parameter for optimization of chiral resolution (R s ) in MEKC. This is because pH usually alters both the charge of the analyte and/or chiral selector (surfactant) possessing ionizable groups as well as influencing the magnitude of electroosmotic flow (EOF).…”
mentioning
confidence: 99%